Clinical importance in the early identification of non-accidental trauma in pediatric population: A comparative study among patients of a high – Complexity reference hospital - Luz Nélida Garzón; María Daniela Moreno; Maria Alejandra Hernández; Ivan Molina; Fernando Fierro; Juan Valero (Journal of Pediatric Surgery Open, 2023)
Aim: To compare the pediatric population that presented with accidental and non-accidental abdominal trauma treated in a reference hospital in Bogotá, Colombia. Methods: Comparative retrospective case series study of children who presented with accidental abdominal trauma (AT) and non-accidental abdominal trauma (NAT) was carried out. The children were treated at HOMI Fundación Hospital Pediatrico la Misericordia from June 2013 to December 2019. Statistical analysis was performed calculating measures of central tendency and dispersion. Results: The study included 175 patients. There was no gender predilection. The most common trauma mechanism in AT was fall (35.17 %) and in NAT was physical aggression (40 %). No difference was found in the dispersion of the Injury Severity Score (ISS). The requirement for surgical approach was higher in the NAT group (63.33 % vs 25.52 %). This group presented with a greater involvement of intra-abdominal organs (75 % vs 52.95 %), greater involvement of the small (20 %) and large (20 %) intestines. NAT children also had more multiple intra-abdominal organs involved (25 % vs 11.76 %), longer intensive care unit stay (56.67 % vs 39.31 %), prolonged hospital stay (7.5 days vs 4 days), and higher complications and mortality (6.67 % vs 2.07 %). Conclusions: Non-accidental abdominal trauma has greater morbidity and mortality in children compared to accidental trauma. For this reason, early identification of these cases is important in order to prevent future complications.